PENGARUH KOMUNIKASI INTERPERSONAL DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PADA KANTOR BAZNAS KOTA SERANG - Evelita Patiara Linda; Ubay Haki; Malik Fatoni (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Employee performance in an organization is influenced by many factors, including motivation, work ethic, work experience, work culture, work discipline and work environment. Employees can carry out their duties optimally, because they are determined by motivation or encouragement to work diligently, and a comfortable work environment that supports employee performance. This happened because it was alleged that there were several problems based on the observations of the researchers. This study aims to examine the influence of interpersonal communication and work environment on employee performance at Baznas Serang City by using a descriptive analytical approach which is a quantitative research. Total population of 30 employees and all populations used as research samples. The main problems and objectives formulated in the research on Employee Work Performance (Y) through , Interpersonal Communication (X1) and Work Environment (X2) at Baznas Serang City, then this research method is a descriptive method of analysty that is to look at causal relationships. Based on the research analysis obtained the value of coefficient of determination (R2)=40,3%. Partial test results of variable X1 of 3,593 and X2 of 3,275 were greater than 1,998 and sig. values < 0.05. The results of the study simultaneously obtained the results of Fcount = 20,922 > Ftable = 3,150. Based on the results of the study, it can be concluded that the influence of the variable Interpersonal Communication and Work Environment partially and simultaneously on Work Performance has a significant and positive influence